On the stability and Hopf bifurcation of the non-zero uniform endemic equilibrium of a time-delayed malaria model - Ncube, Israel (Nonlinear Analysis: Modelling and Control, 2016)
This article considers a time-delayed mathematical model of immune response to Plasmodium falciparum (Pf) malaria. Infected red blood cells display a wide variety of surface antigens to which the body in turn responds by mounting specific immune responses as well as cross-reactive immune responses. The model studied here tracks these infected red blood cells as well as the two types of immune responses. It is assumed that the immune responses are time-delayed, and hence a system of nonlinear delay differential equations is considered. The goal of the paper is to provide a vigorous analysis of the stability and Hopf bifurcation of the non-zero uniform endemic equilibrium of the mathematical model.